Defects in Surface Chemistry—Reductive coupling of Benzaldehyde on Rutile TiO2(110). Issue 25 (13th May 2014) - Clawin, Peter M.; Friend, Cynthia M.; Al‐Shamery, Katharina
Abstract: The surface chemistry of oxygen and oxygenates on Rutile TiO2 (110) is of great interest for various applications such as heterogeneous catalysis and photo catalysis. Though it is generally accepted that surface defects are active sites, the role of subsurface defects is under debate. We have therefore investigated the influence of the bulk defect density on the reductive coupling of benzaldehyde to stilbene as a model system. Using IRRAS we identify stilbene diolate as a reduction intermediate. The concentration of this intermediate is proportional to the bulk defect density, whereas adsorption of benzaldehyde at lower temperatures is not affected, which indicates a dominant role of Ti interstitials at temperatures above 400 K. Abstract : Defect detective! The surface chemistry of oxygen and oxygenates on Rutile TiO2 (110) is of great interest for various applications, and the role of different kinds of defects is hotly disputed. A systematic study of the influence of the bulk defect density in the reductive coupling of benzaldehyde to stilbene reveals that it is proportional to the yield of stilbene and an intermediate. These results indicate a prominent role of interstitial defects.